Effect of drying methods on phenolic compounds and antioxidant activity of Capparis spinosa L. fruits - Shima Babaei Rad; Hasan Mumivand; Saeed Mollaei; Ali Khadivi (BMC Plant Biology)
Abstract Background Drying is a critical post-harvest process for medicinal plants, which are typically high in moisture and microorganisms. To prevent spoilage and quality loss, it is essential to dry these plants promptly. The drying method significantly impacts the levels of secondary metabolites and the organoleptic characteristics of medicinal plants. This study aimed to investigate the effects of various drying methods on the total phenolics, flavonoids, anthocyanins, antioxidant activity, and phenolic acids in caper (Capparis spinosa L.) fruits. The experiment was performed using a completely randomized design with three replications and included 11 treatments: shade drying, sun drying, oven drying (at 50 °C, 60 °C, and 70 °C), microwave drying (at 300 W, 600 W, and 900 W), freeze-drying, salt-drying, and a fresh plant sample as a control. Results Among the drying methods tested, microwave drying consistently produced the highest levels of flavonoids, anthocyanins, and antioxidant activity, regardless of wattage. Specifically, the highest total phenol content was observed in samples dried at 900 W microwave, 600 W microwave, and 70 °C in the oven (5.3, 5.37, and 5.31 mg GAE/g DW, respectively). Drying at 600 W microwave yielded the highest levels of caffeic, cinnamic, ferulic, vanillic, and protocatechuic acids (13.03, 3.85, 4.28, 9.73, and 5.6 µg/g, respectively) while drying at 900 W microwave also resulted in elevated levels of caffeic, ferulic, protocatechuic, and p-coumaric acids. The 70 °C oven drying method also showed high levels of caffeic, cinnamic, ferulic, vanillic, and protocatechuic acids. Freeze-drying achieved the highest levels of rosmarinic, gallic, and m-coumaric acids (320.17, 175.3, and 12.99 µg/g, respectively), while shade drying produced high levels of p-hydroxybenzoic, cinnamic, ferulic, m-coumaric, protocatechuic, and p-coumaric acids. Conclusions Overall, microwave drying (especially at 600 W), oven drying at 70 °C, and freeze-drying emerged as effective alternatives to traditional drying methods. These methods not only preserved the color, texture, and taste of the fruits but also enhanced their bioactive compound levels.